Pharmacokinetics, Safety, and Tolerability of Glecaprevir and Pibrentasvir in Healthy White, Chinese, and Japanese Adult Subjects. (11th August 2017) - Lin, Chih‐Wei; Dutta, Sandeep; Ding, Bifeng; Wang, Tianli; Zadeikis, Neddie; Asatryan, Armen; Kort, Jens; Campbell, Andrew; Podsadecki, Thomas; Liu, Wei
Abstract: Glecaprevir and pibrentasvir are direct‐acting antiviral agents being developed as combination therapy for the treatment of chronic hepatitis C virus infection. The aim of the present studies was to assess the effect of race and ethnicity (white, Han Chinese, Japanese) on the pharmacokinetics and safety of multiple oral doses of glecaprevir and pibrentasvir given alone and in combination. Two multiple‐dose, single‐center, phase 1 studies were conducted in healthy adult male and female subjects (n = 170) of respective Asian and white race/ethnicity. Glecaprevir (100, 200, 300, or 700 mg once daily) and pibrentasvir (80, 120, or 160 mg once daily) were administered alone for 7 days followed by the combination of both direct‐acting antiviral agents for another 7 days. Intensive blood sampling was performed, and pharmacokinetic parameters were estimated by noncompartmental analyses. ANOVA was employed to evaluate for differences of steady‐state glecaprevir and pibrentasvir exposures between Asian (Japanese or Han Chinese) and white subjects. Glecaprevir and pibrentasvir exposures in Han Chinese and Japanese were similar to those in whites across dose levels. The nonlinear dose‐exposure relationships for glecaprevir and pibrentasvir were similar across Japanese, Han Chinese, and white subjects, and the safety profiles of the agents were comparable across these groups. The results of these studies demonstrate that race/ethnicity has no clinically meaningful impact on direct‐acting antiviral agent exposures, safety, or tolerability of the glecaprevir and pibrentasvir combination. This is supported in part by the large global registration program of the pangenotypic, coformulated fixed‐dose glecaprevir/pibrentasvir regimen and allows for inclusion of diverse ethnic populations.